A study on the use of medicinal plants for the treatment of Diarrhoea and Dysentery in Khag tehsil of District Budgam of Jammu and Kashmir - Mir, Tawseef Ahmad; Khare, Rakesh Kumar; Jan, Muatasim (Journal of Medicinal Herbs and Ethnomedicine, 2021)
People are using medicinal plants to alleviate diseases since the time immemorial. The present paper enumerates a total of 25 medicinal plants belonging to 19 families used for the treatment of diarrhoea and dysentery diseases in Khag tehsil of district Budgam, Jammu and Kashmir. Asteraceae was the dominant family. Leaves were found to be dominant plant used for the preparation of herbal remedies. It was found that in this era of modern medicine, people are still relied on traditional medicine to get their primary health care. It was also revealed medicinal plants are under serious threat and needs to be conserved as so as to enjoy this legacy in future too.